Pengaruh Literasi Teknologi dan Pengembangan Inovasi Pendidikan Terhadap Minat Belajar Mahasiswa - Nur Eliza, Julia; Syevyilni Wisda, Rini (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
This research aims to determine the influence of the application of technological literacy and the development of educational innovation on students' interest in learning at the Kerinci State Islamic Institute (IAIN). This research uses quantitative methods with a simple linear regression approach. Data was obtained from 120 respondents using a questionnaire. The sampling technique uses Random Sampling. The research results show that from the "F" value at a significance level of 5%, the Ftable is 22.70 and the Fcount is 59.148, which is much larger than the Ftable. Because Fcount > Ftable, the alternative hypothesis is accepted while the null hypothesis is rejected. Thus, there is a significant influence between the digital literacy variable (X1) and the development of educational innovation (X2) on interest in learning (Y).